Um estudo das perguntas no discurso do professor de Matemática - Rogeri, Norma Kerches de Oliveira (2005)
This work has as objective to analyse the dialogue between teachers and students from 5 th to 8 th grades in Ensino Fudamental and Medio Levels, in Math classrooms, mainly the questions formulated by teachers, searching for the role of social interaction and discursive aspects between teachers and students in the teaching and learning process and the relations between the conceptions involved in this relation and their speech in classroom. During the investigating process of verbal communication, we tried to identify some clues about the role of teacher s speech in Math classes, specially the questions asked by students. We noticed that teachers consider it a fundamental part of the development of Math classes to guarantee student commitment and mainly the possibility of confirming the learning achievements. Moreover, the question corresponds to a speech act largely used by teachers, who often use some to keep the students attention and control the process during the class and/or they use others to evaluate student s understanding of this process. We also figured out that although teachers explicit their conception about teaching and learning focusing on the student and in his active role in knowledge building, being the teacher only the mediator of the process, the practice shows the opposite, which means that the teaching-learning process is centered in teachers, and students only answer questions which require attention and memory. Questions which involve thinking, argumentation and investigation were hardly founded in the three analysed cases. In a inposterioriln reflection made by the involved teachers about their practice in classroom showed on the tapes, we saw an excellent possibility to be exploited in teacher s formation